Kinetics of osmotic dehydration and air-drying of pumpkins (Cucurbita moschata) - Castilho Garcia, Carolina; Aparecida Mauro, Maria; Kimura, Mieko (Elsevier B.V., 2007)
Kinetics of osmotic dehydration (OD) and effects of sucrose impregnation on thermal air-drying of pumpkin slices were investigated. A simplified model based on the solution of Fick's Law was used to estimate effective diffusion coefficients during OD and air-drying. In order to take into account shrinkage, average and variable thicknesses were considered. Pumpkin slices were dehydrated in sucrose solutions (40%, 50% and 60%, w/w, 27 degrees C. The effective water diffusion coefficients were higher than the sucrose, and low diffusivity dependence with solution concentration was observed. Samples non-treated and pre-treated in 60% osmotic solutions during one hour were dried in a hot-air-dryer at 50 and 70 degrees C (2 m/s) until equilibrium was achieved. Pre-treatment enhanced mass transfer during air-drying. Great volume reduction was observed in pre and non-treated dried samples. Using variable thickness in the model diminished the relative deviations between predicted and experimental OD and drying data. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: Diffusion coefficient; osmotic dehydration; convective drying; shrinkage; pumpkin